Exploring the relationship between trunk flexibility and arterial stiffness measured by pulse wave velocity: A systematic review and meta-analysis. - Iván Cavero-Redondo; Helder Fonseca; Iris Otero-Luis; Lucimere Bohn; Carla Geovanna Lever-Megina; Nerea Moreno-Herraiz; Alicia Saz-Lara (PLoS ONE)
Background As individuals age, the risk of cardiovascular disease (CVD) increases, largely due to progressive stiffening of the arteries. This relationship underscores the critical need to monitor arterial stiffness as a predictor of CVD outcomes. While aerobic exercise has demonstrated benefits for vascular health, the influence of flexibility, particularly trunk flexibility, on arterial stiffness remains underexplored. Thus, this study aimed to analyse the overall relationship between trunk flexibility and arterial stiffness across different age groups (young, middle-aged, and older adults) and according to sex. Methods A systematic review and meta-analysis were conducted following the MOOSE and JBI Manual for Evidence Synthesis on systematic reviews of etiology and risk guidelines. Searches in PubMed, Scopus, and Web of Science identified studies investigating the association between trunk flexibility and arterial stiffness measured by pulse wave velocity. Data extraction, quality assessment, and statistical analyses were performed following predefined criteria. Results Five studies involving 2797 participants were included. Poor trunk flexibility was associated with increased arterial stiffness compared to high flexibility (pooled standardized mean difference = -0.27, 95% CI: -0.39, -0.14), with substantial heterogeneity observed. Subgroup analyses by sex and age revealed significant associations predominantly in men and older individuals. Sensitivity analyses confirmed the robustness of the findings, and meta-regression models showed no significant differences according to age, BMI, or blood pressure. No evidence of publication bias was found. Conclusion Poor trunk flexibility is linked to elevated arterial stiffness across diverse demographic groups, highlighting its potential as a surrogate marker for cardiovascular health. Physiological mechanisms involving connective tissue integrity and neural regulation may underpin this relationship. Understanding the role of flexibility in arterial health could inform targeted interventions to mitigate age-related increases in arterial stiffness and reduce cardiovascular disease risk. However, further research is needed to validate these findings and explore potential sex-specific differences.